Virtual surgery and orthopaedic surgery: towards training using haptic technology - Hauck, Robert (2017)
Medical education and practical training in surgery is changing, by shifting from an on the job learning paradigm, which possesses problems such as that it is unpredictable, dependent on clinical needs and that patient safety may be jeopardised, to an evidence-based surgical skills training driven by curricular needs, and acquiring basic surgical skills prior to assisting in the operating theatre and thus reducing operation duration. Towards achieving this goal, virtual reality (VR) simulators are used in minimally invasive surgery for technical skills training at the beginning of the learning curve, but have not yet been adapted for open surgery due to its complexity for simulation. This thesis investigated the potential of using a VR simulator for training in orthopaedic hand surgery, with an emphasis on providing a meaningful, effective and motivating addition to current training methods for surgical procedures.